TransJakarta Service Evaluation in Controlling COVID-19 Transmission Using Twitter Sentiment Analysis - Siti Nurlaela; Andrew William (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
This study attempted to understand passenger perception of using public transport by utilizing Twitter data about the services of the TransJakarta Busway. Tweets were the main data source to capture users’ responses toward these services. Users’ perceptions were analyzed by sentiment analysis using a naïve Bayes algorithm. Furthermore, content analysis was used to inform improvements in service maintenance. The findings showed that the pandemic had a major impact on TransJakarta services, from a decrease in users, route closures, and fleet reductions to changes in user behavior. Most Tweets were negative regarding (1) poor bus frequency, leading to long queues and passenger overcrowding at bus stops and inside buses; (2) failure to maintain social distancing measures; (3) frequent violations of the 50% bus capacity reduction during peak hours, and showing a lack of consideration in measuring demand size during peak hours; (4) staff’s weak control of implementing the health protocol exacerbated poor services. This study suggests service improvement based on peak hour demand analysis to offset the implications of a 50% capacity restriction by providing proper bus frequencies and headway arrangements considerable enough to avoid crowding, followed by optimal monitoring of health protocol by staff. Tweet data may inform poor management in controlling the transmission of COVID-19 on public transportation. Hence, using Twitter data could replace conventional data collection methods like user interviews. Beneficial information from Tweet data can be captured at relatively low costs. Therefore, it may aid the evaluation of PPKM policy implementation to create more resilient public transportation during pandemics.